The Effects of Soil Resistivity on The Corrosion Resistance of Carbon Steel - Syanatha Putri Salsabila; Rini Riastuti (MBI, 2025)
Indonesia, as a tropical country with high humidity, faces corrosion challenges in the underground infrastructure of the oil and gas industry, causing significant economic losses. This study analyzed the effect of soil characteristics on the corrosion rate of carbon steel using the weight loss and linear polarization methods. The weight loss method was used to determine the corrosion rate based on the mass reduction of the sample, while the linear polarization method evaluated the corrosion kinetics through icorr and polarization resistance values. The results showed that soil characteristics, especially moisture and resistivity, had a significant effect on the corrosion rate. Pakis Karawang beach sand soil with pH 5.2, humidity 87%, and resistivity 59.03 Ω-cm had the highest corrosion rate of 42.57 mpy and the lowest polarization resistance of 11.16 Ω. In contrast, the UI Native Forest Ravine soil showed the lowest corrosion rate of 16.89 mpy with the highest polarization resistance of 2,820.11 Ω. These findings confirm that environmental factors, particularly soil type, should be considered in corrosion mitigation strategies to improve the resilience of underground infrastructure.